Analysis of iodine-131-induced early thyroid hormone variations in Graves' disease. Issue 11 (November 2016) - Xu, Feng; Gu, Aichun; Pan, Yifan; Yang, Liwen; Ma, Yubo
Abstract : Objective: This prospective study aimed to assess iodine-131 ( 131 I)-induced early thyroid hormone variations in Graves' disease (GD) and determine the associated factors. Materials and methods: One hundred and seventy-one GD patients treated with 131 I were evaluated (47 men, 124 women). 131 I was administered at 9.0±4.9 mCi on average. Serum free triiodothyronine and free thyroxin were measured within 24 h before treatment and 8 (3–14) days after treatment. Patients were divided into increase, no change, and decrease groups, respectively, on the basis of hormone variations after treatment. χ 2 -Test, analysis of variance, and the Kruskal–Wallis test were used to compare groups in terms of sex, age, course of disease, thyroid stimulating hormone receptor antibodies, antithyroid drug (ATD) pretreatment time, time of ATD discontinuation before 131 I treatment, 24 h thyroid 131 I uptake, thyroid weight, 131 I activity, and 131 I activity/thyroid weight (μCi/g). The Spearman method was used for correlation analyses. Results: Twenty-seven, 20, and 124 cases were assigned to increase, no change, and decrease groups, respectively. Significant differences were found among groups in the time of ATD discontinuation before 131 I treatment [the median duration for methimazole was 11 (5–26), 16 (10–30), and 21 (1–30) days, P =0.000, the median duration for propylthiouracil was 12.5 (5–24), 22 (11–26), and 26 (21–30) days, P =0.000], thyroid weight (93.5±33.6, 90.3±48.8, and 74.1±26.0 g, P =0.003), and μCi/g (84.8±11.8, 100.4±24.9, and 121.1±44.0 μCi/g, P =0.000). Interestingly, μCi/g was negatively and positively correlated to the possibility of hormone increase and decrease, respectively. No significant differences were found in the other parameters assessed. Conclusion: At the early stage of 131 I treatment for GD, few patients showed increased thyroid hormone levels. Key factors may include time of ATD discontinuation before 131 I treatment and μCi/g. High μCi/g might decrease thyroid hormone levels in early treatment, making it safe.